Pengaruh Islamicity Performance Index dan Debt Equity Ratio Terhadap Profitabilitas dengan Intellectual Capital sebagai Variabel Moderasi Periode 2016-2020 - Afandi, Ahmad; Haryono, Slamet (IAIN Kudus, 2022)
The purpose of this study was to determine the effect of Islamicity Performance Index and Debt Equity Ratio on Profitability with Intellectual Capital as a moderating variable. This study uses firm size as a control variable. The type of research used is quantitative research using Moderate Regression Analysis (MRA) and using secondary data in the form of panel data at Islamic Commercial Banks (BUS) for the 2016-2020 period. Data processing uses the STATA application version 12. The population in this study is Islamic Commercial Banks in Indonesia for the 2016-2020 period. The sampling technique used purposive sampling, namely using certain criteria so as to produce 7 Islamic Commercial Banks as samples. The results showed that the Profit Sharing Ratio, Zakat Performance Ratio, Director-Employee Welfare Ratio, Islamic Income vs Non-Islamic Income had no effect on Profitability. While the Debt Equity Ratio has an effect on Profitability. In addition, Intellectual Capital is not able to moderate the Profit Sharing Ratio, Zakat Performing Ratio, Islamic Income vs Non Islamic Income Ratio to Profitability and is able to moderate the Director-Employee Welfare Ratio, Debt Equity Ratio. This research is expected to be useful for banks as a source of information and references that can be used as consideration in making decisions and increasing company profitability